Insecticide activity of botanical formulates on the fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) - López, Jennifer J.; Chirinos, Dorys T.; Ponce, Wilmer H.; Ramon F.; Alarcón, Jennifer P. (Revista Colombiana de Entomología, 2022)
The fall armyworm, Spodoptera frugiperda constitutes the most important pest of corn, Zea mays, and mainly synthetic chemical insecticides are used for its control. The use of botanical compounds is a potentially effective alternative for pest control. The effect of formulations of Eucalyptus globulus, Jatropha curcas, Petiveria alliacea, Ricinus communis and Ruta graveolens, (A) at concentrations of 5%, 10% and 15% (B) on mortality, food inhibition and weight of larvae of S. frugiperda was evaluated. Using second and third instar larvae, spray and choice bioassays were performed using a factorial design AxB + 3 controls [chemical insecticide (cypermethrin), commercial botanical (azadirachtin) and absolute control (water)]. Of the botanical compounds, mortality was higher when J. curcas oil (33.7%) and P. alliacea hydrolate (26.2%) were applied at. 15 mL.L-1. Larvae fed with corn leaves soaked with the three concentrations of P. alliacea and R. graveolens hydrolates showed 71-76% food inhibition, as well as the lowest weight of larvae. The results show the insecticidal activity of the botanical formulations evaluated and their potential for controlling S. frugiperda.